Community Based Prevention Strategies for Collective Trauma in Conflict Zones of the Middle East - M. Agung Rahmadi; Luthfiah Mawar; Liza Adilia Pury; Naura Aqilah Rizal; Wilda Simangunsong; Helsa Nasution; Nurzahara Sihombing; Annisa Ardianti Br Tarigan (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
This meta-analysis provides an in-depth examination of the effectiveness of community-based interventions in alleviating collective trauma experienced by populations in conflict zones of the Middle East, compiling 47 empirical studies (N = 12,483) published between 2000 and 2023. The synthesis indicates a significant impact of community-based interventions on reducing PTSD symptoms, with a substantial effect size (d = 0.82, 95% CI [0.76, 0.88], p < .001) and moderate heterogeneity (I² = 68%), reflecting inter-study variation yet remaining within interpretable bounds. Among the strategies analysed, community psychosocial support programs demonstrated the most pronounced effectiveness (β = 0.74, p < .001), followed by collective narrative therapy (β = 0.68, p < .001) and family-based rehabilitation interventions (β = 0.59, p < .001), all underscoring the relevance of approaches rooted in social networks and interpersonal relations. Moderator analyses revealed that longer program duration, particularly interventions spanning at least 6 months (β = 0.71, p < .001), and active engagement of local leaders (β = 0.65, p < .001) were critical determinants of intervention success. Furthermore, meta-regression findings indicated a strong and consistent correlation between the intensity of community involvement and reductions in collective trauma symptoms (R² = 0.73, p < .001), highlighting that social participation is not merely complementary but constitutes the foundation of program efficacy. In the researchers' view, these findings extend the contributions of prior studies by Hassan et al. (2016) and Morrison & Marrison (2024) by affirming the central role of local wisdom in trauma recovery processes, while offering a conceptual contribution in the form of an integrative framework that merges psychosocial interventions with community cultural values. Consequently, these results provide not only an empirical basis for developing more effective trauma-healing programs in Middle Eastern conflict zones but also underscore the urgency of contextual adaptation to ensure that interventions meet the most essential needs of affected populations.